Patient’s and the Therapist’s Attachment Representations, Attachment to Therapists, and Self-Esteem-Change Through Psychotherapy - Petrowski, Katja; Berth, Hendrik; Beiling, Peter; Renner, Vanessa; Probst, Thomas (Frontiers in Psychology, 2021)
Objectives: The present naturalistic study aims to investigate the differential effects of the patient’s and the therapist’s attachment representations on the attachment to the therapist as perceived by the patient, and their impact on self-esteem-change through psychotherapy. Methods: Attachment variables of N = 573 patients as well as N = 16 therapists were assessed. Attachment representations were measured for therapists and patients via the Bielefelder Questionnaire for Client Attachment Exploration, the Relationship Specific Attachment to Therapist Scales and the Adult Attachment Interview. The patient’s attachment to therapists was evaluated and patients’ self-esteem was measured via the Frankfurter Selbstkonzeptskalen at the beginning and end of psychotherapy. Results: Although there were significant effects of the patient’s attachment representations on the perceived attachment to the therapist as well as between the perceived attachment to the therapist and the amount of self-esteem-change, the therapist’s attachment style had no significant influence on the perceived attachment to the therapist. Conclusion: Self-esteem-change through psychotherapy is influenced by the actually formed attachment relationship as perceived by the patient. The patient’s attachment representations but not the therapist’s attachment style contributes to the actual patient’s attachment to the therapist.